A hybrid wind/ solar energy converter for household application - Li, Fei (2016)
Wind and solar energies have good prospects for both isolated load and grid interconnection. These two energy sources also complement each other. Considering the high cost of electrical energy available from these sources, it is worthwhile to economize in its capital cost. An integrated Wind/solar converter can be very attractive in such a case. This report proposes a hybrid solar / wind energy converter that sum these two sources and supply the net DC energy to a dedicated load.